Banking and Financial Sector in South-eastern Europe - Emidio Cocozza; Alessandro Fabbrini; Enrico Gisolo; Maurizio Gresti; Giacinto Micucci (European Regional Science Association (ERSA), 2001)
Financial and banking systems play a crucial role for the reconstruction of war-worn countries, for the completion of the transition process and for the economic development. Financial systems in transitino countries had to be build from the scratch, often without any consolidated experience in Western-styly financial activities. Notwithstanding considerable efforts on the legal and institutional fronts, financial systems usually remain fragile and too thin in order to fulfill their economic functions. Financial and banking sectors are usually the weakest component of the economic setting through which domestic and external shocks could be exacerbated and became pervasive. Aim of this paper is to summaries the reform efforts and the structural evolution of financial system, particularly of the banking secto in Europea south-east countries (Albania, Bosnia H., Bulgaria, Croatia, Macedonia, Romania, Yugoslavia plus Slovenia. Reforms and economic development in this area are at a very different stage but it could be of some interest to summaries some common regional features such as development patterns in the last decade, banking reforms, size and role of financial and banking crisis. This could be done in the first part opf the paper; country specific profile could be added in a second part.
Keywords: 330